METHODICAL ASPECTS OF TEACHING EFFICIENCY IN SMART-UNIVERSITY - Anzhelika V. Rychkova; Alexander A. Smirnov (Открытое образование (Москва))
Instrumentation development disclosed in accordance with the basic principles of Smart-University. Suggest ways to improve the use of the Electronic Campus and grade-rating system (GRS). Scrum methodology approaches and their adaptation to build Smart-University.